Management Dysfunctional Behaviour toward Financial Statements: Income Smoothing Practice in Indonesia’s Mining Industry Sector - Sigit Handoyo; Safri Fathurrizki (University of Merdeka Malang, 2018)
Companies tried to maintain reported fluctuations in earnings and intervene them to the desired level. With the practice of income smoothing, the information was presented in financial statements; especially income statement became invalid so that it will mislead information to the users. We analyzed the factors influencing the income smoothing practice. Populations in this study were 45 mining companies listed on Indonesian Stock Exchange (IDX). The data used in this study was a secondary data screened by using purposive sampling method. Variables used in this research were company size measured by total assets, profitability proxied by return on assets, dividend payout ratio was proxy by comparing the dividend per share divided by earning per share, financial leverage was proxied by debt to total assets, and income smoothing was measured using Eckel index as dependent variable. This study used logistic regression tools. We found that dividend payout ratio and financial leverage gave significant positive effect to income smoothing practice. However, the size of the company and profitability did not affect to influence income smoothing practice. The investor who willing to invest in shares, it was important to scrutinize dividend payout ratio and financial leverage level of the future company.JEL Classification: L25, G35DOI: https://doi.org/10.26905/jkdp.v22i3.1820